2016
DOI: 10.1287/mnsc.2014.2115
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Workplace Stressors and Mortality and Health Costs in the United States

Abstract: E ven though epidemiological evidence links specific workplace stressors to health outcomes, the aggregate contribution of these factors to overall mortality and health spending in the United States is not known. In this paper, we build a model to estimate the excess mortality and incremental health expenditures associated with exposure to the following 10 workplace stressors: unemployment, lack of health insurance, exposure to shift work, long working hours, job insecurity, work-family conflict, low job contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
190
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(205 citation statements)
references
References 59 publications
(50 reference statements)
2
190
0
4
Order By: Relevance
“…For adults, it affects work performance and, for students, academic achievement through reduced productivity, high absenteeism and presenteeism that generate substantial financial burdens. For example, the estimated cost of U.S. workplace stress alone was $125–190 billion per year (5%–8% of national health spending) (Goh et al, 2016). Numerous preventive mindfulness interventions have focused on managing occupational stress and enhancing work efficiency (Cohen-Katz et al, 2005).…”
Section: Contextmentioning
confidence: 99%
“…For adults, it affects work performance and, for students, academic achievement through reduced productivity, high absenteeism and presenteeism that generate substantial financial burdens. For example, the estimated cost of U.S. workplace stress alone was $125–190 billion per year (5%–8% of national health spending) (Goh et al, 2016). Numerous preventive mindfulness interventions have focused on managing occupational stress and enhancing work efficiency (Cohen-Katz et al, 2005).…”
Section: Contextmentioning
confidence: 99%
“…In Switzerland, one out of four employees reported a significant amount of exhaustion, the core symptom of job burnout in 2010; already in 2000, work stress-related costs added up to CHF 4.2 billion, equaling the amount for the country’s military spending [2]. Similarly, 26 % of workers in the U.S. reported that they are often or very often burned out or stressed by their work [3], with workplace stress being responsible for up to $190 billion in annual healthcare costs in the United States [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Mental and physical health problems associated with workplace psychosocial risk factors are a significant, well-documented health issue Goh et al, 2015;Leka et al, 2008;.…”
mentioning
confidence: 99%